Food Insecurity in Older Adults: Results From the Epidemiology of Chronic Diseases Cohort Study 3 - Fernandes, Simone G.; Rodrigues, Ana M.; Nunes, Carla; Santos, Osvaldo; Gregório, Maria J.; de Sousa, Rute Dinis; Dias, Sara; Canhão, Helena (Frontiers in Medicine, 2018)
Introduction: The public health problem food insecurity also affects the elderly population. This study aimed to estimate the prevalence of household food insecurity and its associations with chronic disease and health-related quality of life characteristics in individuals ≥65 years of age living in the community in Portugal. Methods: The data were collected from the Epidemiology of Chronic Diseases Cohort Study 3 (EpiDoC3) - Promoting Food Security Study (2015–2016), which was the third evaluation wave of the EpiDoC and represented the Portuguese adult population. Food insecurity was assessed using a psychometric scale adapted from the Brazilian Food Insecurity Scale. The data on sociodemographic variables, chronic disease, and management of chronic disease were self-reported. Health-related quality of life were assessed using the European Quality of Life Survey (version validated for Portuguese population). Logistic regression models were used to determine crude and adjusted odds ratios (for age group, gender, region and education). The dependent variable was the perceived level of food security. Results: Among older adults, 23% were living in a food-insecure household. The odds of living in a food-insecure household were higher for individuals in the 70–74 years age group (odds ratio (OR)=1.405, 95% confidence interval (CI) 1.392–1.417), females (OR=1.545, 95% CI 1.534–1.556), those with less education (OR=3.355, 95% CI 3.306–3.404), low income (OR=4,150, 95% CI 4.091–4.210), and those reporting it was very difficult to live with the current income (OR=16.665, 95% CI 16.482–16.851). The odds of having a chronic disease were also greater among individuals living in food-insecure households: diabetes mellitus (OR=1.832, 95% CI 1.818–1.846), pulmonary diseases (OR=1.628, 95% CI 1.606–1.651), cardiac disease (OR=1.329, 95% CI 1.319–1.340), obesity (OR=1.493, 95% CI 1.477–1.508), those who reduced their frequency of medical visits (OR=4.381, 95% CI 4.334–4.428), and who stopped taking medication due to economic difficulties (OR=5.477, 95% CI 5.422–5.532). Older adults in food-insecure households had lower health-related quality of life (OR= 0.212, 95% CI 0.210–0.214). Conclusions: Our findings indicated that food insecurity was significantly associated with economic factors, higher values for prevalence of chronic diseases, poor management of chronic diseases, and decreased health-related quality of life in older adults living in the community.